Non-coding RNAs are key players and promising therapeutic targets in atherosclerosis - Yu, Zhun; Yin, JinZhu; Tang, ZhiTong; Hu, Ting; Wang, ZhuoEr; Chen, Ying; Liu, Tianjia; Zhang, Wei (Frontiers in Cell and Developmental Biology, 2023)
Cardiovascular disease (CVD) is the primary cause of death in humans. Atherosclerosis (AS) is the most common CVD and a major cause of many CVD-related fatalities. AS has numerous risk factors and complex pathogenesis, and while it has long been a research focus, most mechanisms underlying its progression remain unknown. Noncoding RNAs (ncRNAs) represent an important focus in epigenetics studies and are critical biological regulators that form a complex network of gene regulation. Abnormal ncRNA expression disrupts the normal function of tissues or cells, leading to disease development. A large body of evidence suggests that ncRNAs are involved in all stages of atherosclerosis, from initiation to progression, and that some are significantly differentially expressed during AS development, suggesting that they may be powerful markers for screening AS or potential treatment targets. Here, we review the role of ncRNAs in AS development and recent developments in the use of ncRNAs for AS-targeted therapy, providing evidence for ncRNAs as diagnostic markers and therapeutic targets.